Well‐Balanced Ambipolar Organic Single Crystals toward Highly Efficient Light‐Emitting Devices - An, Ming‐Hui; Ding, Ran; Zhu, Qin‐Cheng; Ye, Gao‐Da; Wang, Hai; Du, Ming‐Xu; Chen, Shuo‐Nan; Liu, Yu; Xu, Mei‐Li; Xu, Ting; Wang, Wei; Feng, Jing; et al. (Advanced functional materials, 2020)
Carrier mobility is one of the key issues for applications of organic semiconductors in electronic and optoelectronic devices. Organic single crystals possess much higher carrier mobility compared to amorphous films. However, unipolar properties with unbalanced hole and electron transporting ability have been a bottleneck for the high performance of organic single crystal‐based devices. Here, well‐balanced ambipolar organic single crystals are developed by mixing of n‐ and p‐type molecules with maintained single‐crystalline structures. Carrier mobility of the ambipolar single crystals is manipulated by tuning the mixing ratio, and nearly equal hole and electron mobility can be achieved. Highly efficient single crystal‐based organic light‐emitting devices (OLEDs) are demonstrated by employing the ambipolar crystals as the mixed host for a red emitter pentacene to realize efficient exciton confinement and energy transfer within the emissive layer. As a result, maximum luminance of 5467 cd m−2 and current efficiency of 2.82 cd A−1 are achieved, which represents, to the best of the authors’ knowledge, the record performance for the organic single crystal‐based OLEDs to date. The strategy to manipulate the charge‐transport properties of the organic single crystals in this work represents a significant step toward practical applications of the organic single crystals in optoelectronics. Well‐balanced ambipolar organic single crystals are developed by mixing n‐type BTPB and p‐type BSB‐Me molecules, and the hole and electron mobilities are manipulated to be nearly equal. Organic light‐emitting devices based on these ambipolar crystals exhibit a record luminance, current efficiency, and external quantum efficiency. The strategy to manipulate the charge‐transport properties of the organic single crystals in this work represents a significant step toward practical applications of the organic single crystals in optoelectronics.